2017
DOI: 10.1097/bot.0000000000000953
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in Spinal Ankylosing Disorders: A Narrative Review of Disease and Injury Types, Treatment Techniques, and Outcomes

Abstract: Because of the stiffening of the spinal column, patients with spinal ankylosing disorders are preferably evaluated for spinal fractures and ligamentous injuries after even trivial trauma. Spinal injuries in patients with AS are difficult to diagnose on plain radiographs; computed tomography and magnetic resonance imaging are recommended instead. The entire spine should be scanned for multilevel involvement. Although osteoporosis makes fixation of spine implants a significant concern, the literature has reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 98 publications
2
115
1
1
Order By: Relevance
“…In terms of surgical treatments for lumbar spinal disorders accompanying DISH, Otsuki et al reported shortsegment lumbar interbody fusion as a factor in delayed pseudarthrosis and adjacent segment disease (ASD) [20]. Further, numerous studies have reported that surgical treatment for traumatic spine fracture accompanying DISH often requires multi-level fusion to avoid postoperative ASD [21][22][23]. To maintain postoperative sagittal alignment, pelvic screw insertion, as a strong anchor of spinal fixation, became an indispensable technique not only in patients with DISH, but also in many clinical scenarios such as adult degenerative scoliosis, flat-back syndrome and kyphosis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of surgical treatments for lumbar spinal disorders accompanying DISH, Otsuki et al reported shortsegment lumbar interbody fusion as a factor in delayed pseudarthrosis and adjacent segment disease (ASD) [20]. Further, numerous studies have reported that surgical treatment for traumatic spine fracture accompanying DISH often requires multi-level fusion to avoid postoperative ASD [21][22][23]. To maintain postoperative sagittal alignment, pelvic screw insertion, as a strong anchor of spinal fixation, became an indispensable technique not only in patients with DISH, but also in many clinical scenarios such as adult degenerative scoliosis, flat-back syndrome and kyphosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the ethics committee at Toyama University Hospital (Clinical research number [21][22]. Patients provided written consent for participation in this analysis.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…That is, an ankylosed spine tends to fracture as result of minor injuries such as falling because of stress concentration. Such fractures can cause reverse chance fractures that can lead to spinal paralyses, and are often resistant to conservative treatment [ 1 3 ]. Like other conditions with ligament ossification, DISH is thought to result from a multifactorial process whose etiology is not easily identified.…”
Section: Introductionmentioning
confidence: 99%
“…We found 2 case reports of iatrogenic fracture in patients with AS during surgery [ 9 ]. Compared with the normal population with minor trauma, patients with AS are at a higher risk for spinal fracture [ 10 - 14 ], likely because of the higher incidence of osteoporosis or osteopenia [ 14 - 16 ]. In addition, a rigid spine is unable to distribute the stress to the other segments.…”
Section: Discussionmentioning
confidence: 99%